2019
DOI: 10.21037/pm.2019.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary tracheal tumors in children and adolescents

Abstract: Pediatric primary tracheal tumors (PTTs) are rare entities, with an estimated incidence of 0.2% among all neoplasms in children and adolescents. Benign lesions and malignancies are rather equally represented, with subglottic hemangioma, granular cell tumor, carcinoid tumor, and low-grade mucoepidermoid carcinoma being the most common histotypes. Guidelines on management and treatment of pediatric PTTs are not available, and only a few reviews, case reports, and single surgeon/institute experiences have been pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition to surgical resection, bronchoscopic intervention is effective in treating patients with PTT 9 . However, the bene ts of endoscopic local resection of tumors are unclear because endoscopic resection has several limitations, including a high risk of transmural injury, an inability to coagulate larger diameter vessels, and a risk of airway tree dislocation 16 . CT angiography before brilloscopic intervention showed that two patients in the present cohort had large vessels deep within the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to surgical resection, bronchoscopic intervention is effective in treating patients with PTT 9 . However, the bene ts of endoscopic local resection of tumors are unclear because endoscopic resection has several limitations, including a high risk of transmural injury, an inability to coagulate larger diameter vessels, and a risk of airway tree dislocation 16 . CT angiography before brilloscopic intervention showed that two patients in the present cohort had large vessels deep within the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Often, tracheal tumors remain asymptomatic, obstructing 50 to 70% of the trachea without causing noticeable symptoms. Consequently, they are sometimes misdiagnosed as other lung diseases, such as asthma (3). However, common symptoms associated with tracheal tumors include cough, shortness of breath, and nonspecific manifestations like hemoptysis, pneumonia, weight loss, and wheezing.…”
Section: Introductionmentioning
confidence: 99%